Practice characteristics of dual trained pediatric dentistry and orthodontic specialists - Hayakawa, S; Jedrychowski, J R (ASDC journal of dentistry for children, 1994)
Most respondents to this survey are providing both pediatric dental and orthodontic services to their patients. Almost half of the respondents reported that both specialties are fully integrated without separate times or days. Patient treatment time was reported as 41 percent pediatric dental services and 59 percent orthodontic services; when asked how they would like to adjust patient treatment time in ten years, however, the response was 20 percent pediatric dentistry and 73 percent orthodontics. A high percentage of respondents (44 percent) were involved in teaching full or part time or in continuing education courses.